Nathaniel Highmore (1613-1685) - Kutya, S. A. (Морфологія / Morphologia / Morfologìâ, 2013)
The son of the Rev. Nathaniel Highmore, Nathaniel Highmore the Younger (fig.1) was the most celebrated member of the family, who for centuries had given priests, doctors, lawyers and the well-known artist Joseph Highmore (1692-1780) to the world. For more than 100 years, the Highmore were rectors (parish priest) of St. Peter's Church in the small village of Perse Kaundle (near Sherborne, Dorset). The future scientist was born on February 6, 1613 in Fordinbridge (Hampshire). At the end of the school in Sherborne, Highmore studied at Kuins College, and from 1632, Trinity College, Oxford University. In 1635, he received a Bachelor of Arts degree, and three years later - Master of Arts and studied medicine. In 1640, he married Elizabeth Haydock, daughter of a physician from Salisbury Richard Haydock.